Development of TiO2 coated activated carbon foam as cooling pad for direct evaporative cooling system - Radhiyah, Abd Aziz; Ramprabhu, Kandasan; Nurrina, Rosli (Universiti Malaysia Pahang, 2018)
This research aims to examine the property of the ceramic (TiO2) coated activated carbon foam (TiO2-ACF) as a cooling pad. Efficiency of direct evaporative cooling system mostly depends on the cooling pad and hence, the material used in the cooling pad plays a very vital role. Here, the TiO2-ACF pad is fabricated by dipping activated carbon foam into the slurry of TiO2 which has different loading mass. The physical property of the TiO2-ACF such as stability of the cooling pad under constant and vigorous flow of water, absorbability property and photocatalytic properties were analysed. It is concluded that TiO2-ACF cooling pad can be easily fabricated and have an excellent stability and absorbability property.